Asylum matters : on the front line of administrative decision-making - Affolter, Laura (Palgrave Macmillan, 2021)
This open access book examines everyday practices in an asylum administration. Asylum decisions are often criticised as being 'subjective' or 'arbitrary'. Asylum Matters turns this claim on its head. Through the ethnographic study of asylum decision-making in the Swiss Secretariat for Migration, the book shows how regularities in administrative practice and 'socialised subjectivity' are produced. It argues that asylum caseworkers acquire an institutional habitus through their socialisation on the job, making them 'carriers' of routine practices. The different chapters of the book deal with what it means to methodologically study administrative practice: with how asylum proceedings work in Switzerland and with the role different types of knowledge play in overcoming the uncertainties inherent in refugee status and credibility determination. It sheds light on organisational socialisation processes and on the professional norms and values at the heart of administrative work. By doing so, it shows how disbelief becomes normalised in the office. This book speaks to legal scholars, sociologists, anthropologists, human geographers and political scientists interested in bureaucracy, asylum law, migration studies and socio-legal studies, and to NGOs working in the field of asylum. Laura Affolter is a postdoctoral researcher in the Research Group Sociology of Law at the Hamburg Institute for Social Research, Germany, and Associate Researcher at the Institute for Social Anthropology in Bern, Switzerland. Her (co-authored) publications include Taking the 'Just' Decision (2019) and Keeping Numbers Low in the Name of Fairness (2020).
Keywords: Switzerland. -- Staatssekretariat für Migration.; Asylum, Right of -- Switzerland.; Public administration -- Decision making.; Asylum, Right of; Public administration -- Decision making; Switzerland; Human Rights and Crime; Criminal Justice; Migration; Human Geography; Human Rights; Social Justice, Equality and Human Rights; Socio-Legal Studies; Biotechnology; socio-legal; borders; bureaucracy; at the heart of the state; asylum procedure; asylum decision-making; law and discretion; Open Access; Crime & criminology; Human rights, civil rights; Criminal justice law; Migration, immigration & emigration; Politics & government; Electronic book.